Effects of different water-saving irrigation strategies on water and salt dynamics in the Hetao Irrigation District - MI Boyu; JIA Zhijun; CHEN Haorui; CHANG Xiaomin; WANG Huailiang; WANG Shaoli; GUAN Xiaoyan; LIU Yong (Guan'gai paishui xuebao)
【Objective】The Hetao Irrigation District relies heavily on surface water for irrigation, and the balance between water conservation and salt management is a major challenge. In this paper, we investigate the effects of various water-saving strategies on water and salt dynamics in a representative area within the district.【Method】A modeling-based approach was used, in which a coupled water-salt transport model was developed, calibrated, and validated using data collected in 2018 and 2019 from a representative field site. The validated model was then used to simulate soil water and salt dynamics under a baseline scenario and six alternative water-saving scenarios. Simulation results were analyzed to optimize irrigation practices, focusing on their impacts on groundwater levels, soil salt accumulation, and crop evapotranspiration.【Result】Reducing irrigation amounts lowered the groundwater table but increased in salt accumulation. Canal lining reduced water consumption and enhanced soil desalination. Combined use of brackish groundwater and canal water for irrigation led to an increase in salt accumulation. A linear relationship was found between water-saving intensity and decline in groundwater table, in that for every 10% reduction in irrigation water (approximately 34.5 mm), the groundwater table was lowered by 0.183 m. The 0-100 cm soil profile was divided into three zones based on salt dynamics: a desalination zone (0-20 cm), a transition zone (20-40 cm), and a salt accumulation zone (40-100 cm). Groundwater recharge and salt leaching were negatively correlated, in that for every 10 mm increase in recharge, salt leaching decreased by 33.9 g/m2. No significant variation in crop evapotranspiration was found among all scenarios.【Conclusion】Canal lining is an effective method to achieve both water savings and salt control. In contrast, reducing irrigation amount or using mixed irrigation with brackish and canal water tends to increase soil salinity. These findings underscore the importance of selecting appropriate water-saving strategies to balance water conservation and salinity management in arid irrigation districts.